Black American Military Leaders a biographical dictionary - Hawkins, Walter L. (McFarland, 2007)
"This book is a revised edition of the 1993 African American Generals and Flag Officers: Biographies of Over 120 Blacks in the United States Military. It offers detailed, career-oriented summaries for men and women who overcame societal obstacles to become ranking officers in the U.S. military. Included now are members of all branches of the armed services"--Provided by publisher.